Numerical Analysis of Flow Characteristics of Upper Swirling Liquid Film Based on the Eulerian Wall Film Model - Yue, Ti; Chen, Jianyi; Wang, Yaan; Zhu, Fawen; Li, Xiang; Huang, Shan; Zheng, Lele; Deng, Shuang; Shang, Qiao (Frontiers in Chemical Engineering, 2022)
The Upper Swirling Liquid Film (USLF) phenomenon that occurs in the upper cylinder of the Gas-Liquid Cylindrical Cyclone (GLCC) separator is the direct cause of the low separation efficiency of the liquid phase. In this study, firstly, the USLF formation and development was simulated by an improved Eulerian-EWF coupled simulated method. Through introducing a profile-defined inlet boundary and considering entrainment droplets size distributions, the Eulerian-EWF method got reasonable results which agreed well with the experimental. Then, the flow characteristics and changing laws of the USLF including film thickness, film axial velocity and film tangential velocity were analyzed by this method under different gas-liquid flowrates. It suggested that the liquid film thickness often reaches a maximum at the aspect ratio (z-z0)/D=(1.2~3.9) above the tangential inlet, and the film thickness appears to be more sensitive to the gas flow than to the liquid flow. For the film axial velocity, the direction of film velocity on the front and back sides seems to be generally opposite. Finally, typical distributions of above USLF variables were presented and corresponded accordingly, and two obvious rules were found. One is that the position where the thickest liquid film located always corresponds to the position where the axial film velocity turns from positive to negative for the first time. The other is that the tangential film velocity has a strong synchronous relationship with the film thickness. This research might provide somewhat valid information for the future LCO-prevented measurement in GLCC separators.